Case Report: Superior Vena Cava Resection and Reconstruction for Invasive Thyroid Cancer: Report of Three Cases and Literature Review - Chen, Wenjie; Lei, Jianyong; Wang, Yichao; Tang, Xiaojun; Liu, Bin; Li, Zhihui; Zhou, Qinghua (Frontiers in Surgery, 2021)
Background Thyroid cancer with massive invasion into the cervical and mediastinal great veins is extremely rare, and the surgical treatment is controversial, thus posing a great challenge for head and neck surgeons. Here, we report our successful experiences in reconstructing the superior vena cava (SVC) system to treat thyroid cancer with an extensive tumor thrombus growing intraluminally into the SVC. Case Presentation From September 2019 to September 2020, three patients with superior vena cava syndrome(SVCS) caused by tumor thrombus invasion from thyroid cancer were continuously included in this series. After preoperative evaluation, radical resection and reconstruction of the SVC system with expanded polytetrafluoroethylene (EPTFE) grafts were performed. In addition, bypass support from the right internal jugular vein to the right femoral vein was routinely prepared intraoperatively to prevent a rise in central venous pressure (CVP). Postoperatively, SVC-related syndrome improved immediately after the operation. Imaging examination showed good function of the reconstructed venous system. The patients recovered well with no surgical complications and remain under continuous follow-up. Conclusions: Tumor growth into the SVC does not seem to be an absolute contraindication for surgery for thyroid carcinoma. Comprehensive treatment, including reconstruction of the SVC, is effective for relieving symptoms and preventing disease progression and is thus worth advocating. In addition, bypass support from the internal jugular vein to the femoral vein is easy to implement and can improve the safety of the operation.